Hubungan Antara Breastfeeding Self Efficacy (BSE) Pada Ibu Post Dengan Keberhasilan ASI - Aryanti Wardiah; Lidya Ariyanti; Anggita Widya Lestari (Universitas Malahayati Lampung, 2020)
THE CORRELATION BETWEEN BREASTFEEDING SELF EFFICACY (BSE) OF POST PARTUM WOMEN AND BREASFEEDING SUCCESS AT WORKING AREA OF SUMUR BATU HEALTH CENTER Background: A woman in her first breastfeeding practice is usually more sensitive regarding the condition of her infant. She is easily provoked by an assumption that the intake need of the infant cannot be met by the exclusive milk only. Moreover, at the initial time of breastfeeding, the woman breasts do not produce any milk but colostrum in small quantity. The woman with high expectation of baby optimal care without sufficient support may fall to oppressed situation in the postpartum period (postpartum blues). The woman suffering postpartum blues tends to give up breastfeeding in the initial time, experience breastfeeding difficulty, and low breastfeeding self-efficacy. The objective of this study was to identify the correlation between breastfeeding self-efficacy of postpartum women and breastfeeding success at working area of SumurBatu Health Cente.Purpose: This study is a quantitative. The research design was descriptive study to investigate how and why a health phenomenon happened. The approach was retrospective. Methods: The population consisted of 125 women registered at working area of SumurBatu Health Center since January to March 2019 with status of postpartum and or breastfeeding 6-12 month babies. The sample calculation was conducted with Solvin Formulation that resulting 96 respondents. The sampling technique was simple random sampling.Results: The statistical test found that p value was 0.001 or p value 0.05 implying the correlation between breastfeeding self-efficacy of postpartum women and breastfeeding success at working area of SumurBatu Health Center in 2019. The health practitioners at the health center should educate the women about the importance of breastfeeding for 0-6 month babies through counseling and seminar Conclusion: It is known that in the Work Area of the Sumur Batu Bandar Lampung Health Center in 2019, the majority of respondents had low Breastfeeding Self Efficacy totaling 40 respondents (41.7%). It is expected that respondents will be able to increase knowledge about the importance of breastfeeding. Keywords : Breastfeeding Self Efficacy (BSE), Breastfeeding Success INTISARI: HUBUNGAN ANTARA BREASTFEEDING SELF EFFICACY (BSE) PADA IBU POST PARTUM DENGAN KEBERHASILAN ASI DI WILAYAH KERJA PUSKESMAS SUMUR BATU Pendahuluan: Ibu dengan pengalaman pertama menyusui seringkali sangat sensitif terhadap segala sesuatu yang menyangkut keadaan bayinya, sehingga mudah terprovokasi dengan berbagai anggapan yang negatif seperti, bayi tidak akan cukup kenyang bila hanya mendapat ASI, apalagi di awal periode postpartum ibu hanya memproduksi kolostrum yang berjumlah sedikit atau bahkan belum mengeluarkan ASI. Ibu dengan harapan yang tinggi tentang perawatan bayi yang optimal, tetapi tidak ditunjang dengan pengetahuan dan dukungan yang adekuat dapat menyebabkan ibu jatuh pada kondisi stres selama periode postpartum (postpartum blues). Ibu yang mengalami gejala postpartum blues di awal periode postpartum mempunyai kecenderungan berhenti menyusui lebih awal, mengalami berbagai kesulitan dalam hal menyusui dan breastfeeding self effi cacy yang rendah.Tujuan: Tujuan dalam penelitian ini adalah diketahui hubungan antara Breastfeeding Self Efficacy (BSE) dengan keberhasilan ASI pada ibu post partum di wilayah kerja Puskesmas Sumur Batu.Metode: Jenis penelitian yang digunakan dalam penelitian ini adalah kuantitatif. Rancangan dalam penelitian ini menggunakan deskriptif yang artinya penelitian yang menggali bagaimana dan mengapa fenomena kesehatan itu terjadi, dengan menggunakan pendekatan retrospective. Populasi dalam penelitian ini adalah seluruh Ibu post partum dan ibu menyusui ASI 6-12 bulan yang ada di wilayah kerja puskesmas sumur batu Sumur Batu pada Bulan Januari-Maret yaitu sebanyak 125, dalam mengintung sampe menggunakan rumus slovin sehingga sampel minimum yang didapatkan berjumlah 96 responden. Dalam penelitian ini teknik sampling yang digunakan adalah simple random sampling.Hasil:Berdasarkan hasil uji statistik, didapatkan p-value 0,001 atau p-value 0,05 yangKesimpulan: Terdapat hubungan antara Breastfeeding Self Efficacy (BSE) dengan keberhasilan ASI pada ibu post partum di wilayah kerja Puskesmas Sumur Batu Tahun 2019. Diharapkan agar pihak Puskesmas dapat mengadakan pendidikan kesehatan dengan cara mengadakan seminar kesehatan dan memberikan konseling di poli kebidanan dengan sasaran ibu menyusui tentang pentingnya pemberian ASI pada bayi usia 0-6 bulan Kata Kunci : Breastfeeding Self Efficacy (BSE) Keberhasilan Menyusui